2020
DOI: 10.1039/d0cp05197g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, diffusion and aggregation of Ir atoms on graphdiyne: a first-principles investigation

Abstract: Graphdiyne (GDY) is a newly discovered 2D carbon allotrope, widely used as a support for heterogeneous transition metal catalysts. We investigated the binding, electronic structure, diffusion mechanisms and aggregation possibilities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Following structural optimization, the lattice constant of GDY was determined to be 9.46 Å. The bond lengths for C-C on the benzene ring, C sp 2 − C sp attached to the benzene ring, and C sp 3 − C sp 3 and C sp − C sp on the diacetylene chain were found to be 1.43 Å, 1.39 Å, 1.33 Å, and 1.23 Å, respectively, in agreement with prior calculations [20]. For the purpose of doping GDY substrates, we selected six 5d TM atoms: Hf, Ta, W, Re, Os, and Ir.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Following structural optimization, the lattice constant of GDY was determined to be 9.46 Å. The bond lengths for C-C on the benzene ring, C sp 2 − C sp attached to the benzene ring, and C sp 3 − C sp 3 and C sp − C sp on the diacetylene chain were found to be 1.43 Å, 1.39 Å, 1.33 Å, and 1.23 Å, respectively, in agreement with prior calculations [20]. For the purpose of doping GDY substrates, we selected six 5d TM atoms: Hf, Ta, W, Re, Os, and Ir.…”
Section: Resultssupporting
confidence: 84%
“…Notably, GDY boasts a natural porous structure characterized by a triangular hole enclosed by 18 carbon atoms, which provides ample space for the stable introduction of TM atoms and polyatoms. Considerable theoretical or experimental studies on TM single-atom or multi-atom doping of GDY have been reported [20][21][22][23]. Previous studies have shown that a tetrahedral structure composed of four TM atoms can be securely embedded within the triangular hole of GDY, offering excellent catalytic properties [24].…”
Section: Introductionmentioning
confidence: 99%
“…34,45,46 Considering the monodispersed under-coordinated nature of metals in SACs and the dynamic adsorption and conversion of substrates in reaction conditions, the impact of reaction species on metal centers would be more pronounced, and it may stabilize or even drive further evolution of metal centers, switch the reaction mechanisms and contribute to the conversion and product selectivity. [47][48][49][50][51] To this end, mechanism investigations on SAC-catalyzed chemical conversion in conditions relevant to experiments would be more helpful to rationalize the understanding of the observed superior performance of SACs. 34,45 CO oxidation is one of the most investigated heterogeneous reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical activity of the triple carbon bonds of the GDY, the top site of the acetylenic ring is often the most stable adsorption site for single metal atom adsorption. However, according to the previous works, [50][51][52][53] the atoms would automatically migrate to the corner when the transition metal (TM) or noble metal atoms were located at the center of the acetylenic ring. While alkali metals such as Li, Na and K Fig.…”
Section: Chemistry Of LI 3 Omentioning
confidence: 99%